Maximum power point tracking of photovoltaic array using fuzzy logic control - Djaafar Toumi; Djilani Benattous; Ahmed Ibrahim; Bedida Tarek; Messaoud Zobeidi; Khelaifa Fethi; Hicham Serhoud; Yacine Labbi; Raef Aboelsaud; Sergey Obukhov; Mohamed Tayeb Boussabeur (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This research introduces the simulation of photovoltaic (PV) array to track the peak point (MPPT) using fuzzy logic control. Therefore, real time simulation is performed in MATLAB/Simulink based on a PV model, boost converter and fuzzy logic-based tracker. A comparative study is carried out against perturb and observe (P&O) controller. The fuzzy logic technique based tracker can successfully track the maximum power point very fast and has precise control when compared to the P&O algorithm. The overall we conclude that the MPPT using the fuzzy logic technique takes a fast response and can improve the performance of the PV system.